E-Modules for Computer Network Practicum Based on Problem-Based Learning and Peer Tutoring: A Practical Solution to Develop 21st-Century Skills - Mursyida, Lativa; Dewi, Ika Parma; Samala, Agariadne Dwinggo; Ranuharja, Fadhli (Journal of Education Technology, 2024)
Learning in the era of the Fourth Industrial Revolution requires innovation in learning, one of which is through learning media. E module is a learning media that is more efficient and flexible than conventional media. E-modules that are integrated with appropriate learning models can help achieve optimal learning outcomes. This research aims to develop an electronic module (e-module) for Computer Network Practicum based on Problem-Based Learning (PBL) and Peer Tutoring (PT) and test its effectiveness in enhancing 21st-century skills among students. The research method applied is Research and Development (R&D), with module validity and practicality evaluated by experts and students. Effectiveness testing is conducted by comparing post-test results between the experimental group using PBL and PT e-modules and the control group using conventional worksheets. The research findings indicate that the developed e-module has strong validity, is easy to implement, and is effective in improving 21st-century skills among students. The post-test results of the experimental group are also significantly higher than those of the control group. The implications of this research are significant contributions to the development of technology-based teaching materials to enhance the quality of computer network practicum learning. The implementation of PBL and PT strategies in the e-module can be an effective alternative in designing teaching materials oriented towards the development of 21st-century skills, serving as a guide for educators and curriculum developers to enhance innovative learning approaches across various subjects.